Need for Nucleic Acid Testing in Countries with High Prevalence of Transfusion-Transmitted Infections. (12th September 2012) - Jain, Rohit; Aggarwal, Pankaj; Gupta, Gajendra Nath
Abstract : Introduction. In India, family/replacement donors still provide more than 45% of the collected blood. With increasing voluntary blood donation and the still-prevalent infectious diseases in donors, we need to augment transfusion-transmitted infections (TTIs) testing before use. Our study was aimed to know the seroprevalence of TTIs among the donors of Rajasthan and the need for newer technologies like nucleic acid testing (NAT). Materials and Methods. Enhanced chemiluminescence immunoassay (ECi) was used for detection of HBsAg, anti-HIV, and anti-HCV in donor serum. 50% of the blood units which were negative on ECi were randomly selected and subjected to NAT testing for HBV, HCV, and HIV. Results. The total seroprevalence of TTIs is 2.62%. Of the randomly selected donor units negative by ECi, 8 turned out to be reactive on NAT testing: 4 were voluntary and 4 were family/replacement donors. Combined NAT yield (NAT reactive/seronegative) for HIV, HCV, and HBV was 0.034% (1 in 2972 donations). All the 8 reactive samples were positive for HBV DNA. Conclusion. In countries with a high prevalence of TTIs like India there are likely to be a significant number of window period donations that can be identified by NAT which may be implemented in blood centers allover India with serological testing to provide safe blood and cost alone should not be a deterrent to the government and implementing agencies.